Humanistic Geography: How it blends with human geography through methodology - Sapkota, Kanhaiya (Geographical Journal of Nepal, 2017)
Humanistic geography is a genre of geography born in late 1960s. A series of theories came out which criticize the knowledge system of logical positivism. The philosophical fundaments of humanistic geography are existentialism and phenomenology. Yi-fu Tuan, Edward Relph, Anne Buttimer, David Ley, Marvyn Samuels and Nicholas Entrikin are the leaders of humanistic geography. Yi-fu Tuan published the first article about humanistic geography, which was collected in Human Geography (1976). The focus of humanistic geography is on people and their condition. However, in different geographic traditions, humanistic geography is often criticized for its weak methodology. I argue humanistic philosophy, can provide a sound epistemologicalframework in which to organize and strengthen this methodology in human geography research. The topics of geographical knowledge, territory and place, crowding and privacy, livelihood and economics, and religion are briefly noted from the humanistic perspective. The basic approach to these topics is by way of human experience, knowledge, and awareness. The application of this approach is emerging in the Nepalese context, however for long time Nepalese geographers followed the Western Eurocentric view and appear to be content in following western notions and ignored understanding our own social and cultural aspects/landscapes that enrich our knowledge of geography. The researcher claims that there is a need to rethink our research practices towards better understanding of the world with austerity of philosophical and methodological consistency. The Geographical Journal of Nepal Vol. 10: 121-140, 2017